Narodne pjesme za razna kola iz Srednjega Lipovca u Slavoniji s jezičnoga gledišta - Galović, Filip (SlavVaria, 2026)
Folk songs for various folk dance from Srednji Lipovac in Slavonia from a linguistic point of view. The local dialect of Srednji Lipovac is part of the Slavonian dialect, its Posavina subdialect, and it is well known in dialectological literature today. In 2012 was published a collection of poems entitled Pisme iz Srednjeg Lipovca: balade za šetana kola i druge pisme containing a large number of songs written in the vernacular of that region. The paper presents the phonological and morphological features of selected songs and compares them with data recorded during field research, i.e. specific matches and discrepancies are observed.